2021
DOI: 10.1080/10717544.2021.1937380
|View full text |Cite
|
Sign up to set email alerts
|

ROS-responsive dimeric prodrug-based nanomedicine targeted therapy for gastric cancer

Abstract: Gastric cancer (GC) remains a major public health problem. Ursolic acid (UA) is reported to be effective in inhibiting GC; however, its low solubility and poor biocompatibility have greatly hindered its clinical application. Herein, an innovative reactive oxygen species (ROS)-sensitive UA dimeric prodrug is developed by coupling two UA molecules via a ROS-cleavable linkage, which can self-assemble into stable nanoparticles in the presence of surfactant. This new UA-based delivery system comprises the following… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…These transmembrane proteins are overexpressed in various tumor cells but expressed at low levels in normal cells, which allows a specific and selective internalization of nanoparticles (NPs) by cancer cells. 119 This study showed that this nanosystem improved the solubility and extended the blood circulation time of UA. Furthermore, the sensitivity of the thioketal present in the structure of prodrug 76 was also confirmed, which releases the UA molecules in the presence of ROS through the mechanism described in Scheme 20.…”
Section: Thioketalsmentioning
confidence: 78%
See 1 more Smart Citation
“…These transmembrane proteins are overexpressed in various tumor cells but expressed at low levels in normal cells, which allows a specific and selective internalization of nanoparticles (NPs) by cancer cells. 119 This study showed that this nanosystem improved the solubility and extended the blood circulation time of UA. Furthermore, the sensitivity of the thioketal present in the structure of prodrug 76 was also confirmed, which releases the UA molecules in the presence of ROS through the mechanism described in Scheme 20.…”
Section: Thioketalsmentioning
confidence: 78%
“…Furthermore, mice treated with the NPs had no significant decrease in their body weight which confirmed the safety of this methodology. 119 Template for SYNLETT Thieme…”
Section: Thioketalsmentioning
confidence: 99%
“…The subsequent cascade resulted in improved tumor inhibition rates, suggesting that this strategy could represent a useful solution for targeting resistant metastatic niches in breast cancer. Ma et al [ 81 ] constructed a novel ROS- responsive UA-based dimer prodrug by joining two UA molecules through ROS cleavable linkage. This delivery system is characterized by its dimeric prodrug core that can selectively convert into drug molecules in the presence of ROS.…”
Section: Chemical Modulation Of the Tme Using Nanoparticlesmentioning
confidence: 99%
“…The self-assembled polymeric prodrug micelles are very stable in a physiological environment and can reduce unwanted drug leakage of drugs before reaching tumor tissue, thereby effectively inhibiting side effects of chemotherapeutic drugs on normal cells ( Sun et al, 2018 ; Shukla et al, 2022 ; Sun et al, 2022 ). The polymeric prodrug micelles not only have the advantages of improved chemical stability, high DLC and low side effects, but they can also be used as drug carriers, thereby constituting a multidrug codelivery system that can be used for combination therapy and for improving therapeutic efficacy ( Li S. et al, 2020 ; Ma et al, 2021 ). Furthermore, polymeric prodrugs can be designed for exogenous (e.g., ultrasound and light) or endogenous [e.g., reactive oxygen species (ROS), reducing environment and enzymes] stimulus-responsive drug delivery to activate their toxicity and achieve controlled drug release at the tumor site ( Yang et al, 2019 ; Ye et al, 2019 ; Cao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%